1995
DOI: 10.1093/treephys/15.4.211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of needle age, long-term temperature and CO2 treatments on the photosynthesis of Scots pine

Abstract: Naturally regenerated 20-25-year-old Scots pine (Pinus sylvestris L.) trees were grown in open-top chambers in the presence of an elevated temperature or CO(2) concentration, or both. The elevated temperature treatment was administered year-round for 3 years. The CO(2) treatment was applied between April 15 and September 15 for 2 years. The photosynthetic responses of 1- and 2-year-old needles to varying photon flux densities (0-1500 micro mol m(-2) s(-1)) and CO(2) concentrations (350, 700 and 1400 micro mol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 28 publications
11
76
0
Order By: Relevance
“…It is also reported that most of the nitrogen is used for synthesizing components of the photosynthetic apparatus, and net assimilation rates increase linearly with leaf N concentration (Sugiharto et al 1990;Brown et al 1996). Consistent with the previous studies (Wang et al 1995;Chen et al 2005), warming and N fertilization significantly increased A max and U in P. tabulaeformis seedlings W experimental warming effect, F N fertilization effect, W 9 F the interactive effect of warming and N fertilization. NS not significant at the level of P = 0.05, significant at the level of *P = 0.05, significant at the level of **P = 0.01, significant at the level of ***P = 0.001 (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is also reported that most of the nitrogen is used for synthesizing components of the photosynthetic apparatus, and net assimilation rates increase linearly with leaf N concentration (Sugiharto et al 1990;Brown et al 1996). Consistent with the previous studies (Wang et al 1995;Chen et al 2005), warming and N fertilization significantly increased A max and U in P. tabulaeformis seedlings W experimental warming effect, F N fertilization effect, W 9 F the interactive effect of warming and N fertilization. NS not significant at the level of P = 0.05, significant at the level of *P = 0.05, significant at the level of **P = 0.01, significant at the level of ***P = 0.001 (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…6; Zhao and Liu 2009). Soil warming generally increased the value of light compensation point (LCP) in literature (Wang et al 1995). Similarly, our results also implied that warming was favorable for improving LCP of P. tabulaeformis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this study, elevated temperatures significantly enhanced A, A max and R d . This was possibly because that warming provided more optimal temperature conditions for gas exchange (Wang et al, 1995). Moreover, in the present case, artificial warming significantly increased the leaf N concentrations for two age classes regardless of experimental sites.…”
Section: Direct Warming Effect Through Enhancing Photosynthetic Capacitymentioning
confidence: 45%
“…[12] and in seedlings of loblolly pine there was an increase in the optimum temperature for Anet in trees grown under elevated CO 2 . Contrarily, mature Pinus sylvestris (L.) [13] and Betula papyrifera, Picea mariana and Populus tremuloides [14] observed a decrease in Anet with an increase in temperature under both ambient and elevated CO 2 suggesting that there was no interactive effects of temperature by CO 2 treatment interaction. The present study was taken up to investigate the biochemical responses of two tropical tree species of family Meliaceae to elevated CO 2 .…”
Section: Introductionmentioning
confidence: 95%